2010
DOI: 10.1093/occmed/kqq168
|View full text |Cite
|
Sign up to set email alerts
|

The healthy worker effect in US chemical industry workers

Abstract: The low SMRs observed in this study are likely due to differential smoking between the cohort and the background population. Future considerations to control for the HWE should take this into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Since increased age is associated with increased length of military service, the lower mortality in the oldest ages suggests evidence of a Healthy Soldier Survivor Effect (HSSE) – increased time in military service may be providing beneficial health effects. Higher than expected mortality at the youngest ages parallels the association between shorter duration of employment and elevated mortality in HWE studies of the chemical industry [ 28 ]. Additionally, evidence suggests that combat experience may lead younger soldiers to engage in risky and dangerous behaviors such as speeding, drinking and driving, and failure to wear seat belts [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since increased age is associated with increased length of military service, the lower mortality in the oldest ages suggests evidence of a Healthy Soldier Survivor Effect (HSSE) – increased time in military service may be providing beneficial health effects. Higher than expected mortality at the youngest ages parallels the association between shorter duration of employment and elevated mortality in HWE studies of the chemical industry [ 28 ]. Additionally, evidence suggests that combat experience may lead younger soldiers to engage in risky and dangerous behaviors such as speeding, drinking and driving, and failure to wear seat belts [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is due to pre-employment screening and regular medical check-ups as well as self-selection. Scientific medical reports also contain the data on such "healthy worker" phenomenon [12][13][14]. Except coalminers operators constitut portion of AH patients.…”
Section: Resultsmentioning
confidence: 99%
“…To complete the bias analysis, we checked the ‘healthy worker effect’ mentioned e.g. for US American chemistry workers [ 18 ] and workers of the nuclear production complex of Hanford Site [ 19 ]. From 19 studies mentioned, we found 7 with SMR information for nonradiation workers.…”
Section: Discussionmentioning
confidence: 99%